Quality Assurance Methods of Software Applications and Online Services in Institutions of Higher Education - Pavlova, Elitsa (UNWE Yearbook, 2024)
The report examines methods for ensuring the quality of software applications and online services in higher education institutions (HEIs). It highlights key challenges related to security, system complexity, and user diversity. Testing approaches such as performance, compatibility, security, and usability testing are analysed. It emphasizes automation, integration with DevOps processes, and the use of standardized tools. The report offers solutions for reducing vulnerabilities and ensuring software reliability and functionality. The main conclusion is that continuous testing and integrated security are critical for data protection and the smooth operation of university systems.